Association between active tobacco use during pregnancy and infant respiratory health: a systematic review and meta-analysis. Issue 9 (30th September 2020) - De Queiroz Andrade, Ediane; Da Silva Sena, Carla Rebeca; Collison, Adam; Murphy, Vanessa E; Gould, Gillian Sandra; Bonevski, Billie; Mattes, Joerg
Abstract : Objective: To evaluate what is known about active tobacco use during pregnancy and the association with infant respiratory health. Design: Systematic review and meta-analysis using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data sources: MEDLINE, EMBASE, Cochrane, CINAHL, and Maternity and Infant Care were searched thoroughly until June 2020. Eligibility criteria for selecting studies: We included case–control and cohort studies estimating the association between active tobacco use during pregnancy and infant respiratory health (wheezing and apnoea) and lung function parameters in the first 12 months of life. Data extraction and synthesis: Extraction and risk of bias assessment were conducted by two independent reviewers. The odds ratio, relative risk and mean differences were pooled with a 95% CI using the generic inverse variance method. Heterogeneity was assessed and expressed by percentage using I 2 . Results: We identified 4423 abstracts, and 21 publications met the eligibility criteria. Pooled OR showed an increase in wheezing episodes in infants born to mothers who were active tobacco users during pregnancy (OR 1.50, 95% CI 1.27 to 1.77, p<0.01). Mixed results were found on lung function parameters, and a meta-analysis including two studies with comparable methodology showed a trend towards reduced maximum flow rate at functional residual capacity of −34.59 mL/s (95% CI −72.81 to 3.63, p=0.08) in 1-month-old infants born to women who smoked during pregnancy. A higher risk of apnoea was described for infants born to mothers who used smokeless tobacco during pregnancy, while the results in infants born to women who actively smoked tobacco during pregnancy were non-conclusive. Conclusion: Infants born to mothers who actively smoked during pregnancy are at higher odds of having wheeze and may have lower lung function. Smokeless tobacco use in pregnancy may increase the risk of apnoea in infancy. PROSPERO registration number: CRD42018083936.